Glutamine promotes antibiotic uptake to kill multidrug-resistant uropathogenic bacteria - Zhao, Xian-Liang; Chen, Zhuang-Gui; Yang, Tian-Ci; Jiang, Ming; Wang, Jie; Cheng, Zhi-Xue; Yang, Man-Jun; Zhu, Jia-Xin; Zhang, Tian-Tuo; Li, Hui; Peng, Bo; Peng, Xuan-Xian (Science translational medicine, 2021)
The prevalence of multidrug-resistant bacteria has been increasing rapidly worldwide, a trend that poses great risk to human and animal health and creates urgent need for pharmaceutical and nonpharmaceutical approaches to stop the spread of disease due to antimicrobial resistance. Here, we found that alanine, aspartate, and glutamate metabolism was inactivated, and glutamine was repressed in multidrug-resistant uropathogenic using a comparative metabolomics approach. Exogenous glutamine promoted β-lactam–, aminoglycoside-, quinolone-, and tetracycline-induced killing of uropathogenic and potentiated ampicillin to eliminate multidrug-resistant , , , , , and . Glutamine-potentiated ampicillin-mediated killing was effective against biofilms of these bacteria in a mouse urinary tract infection model and against systemic infection caused by , , , or in a mouse model. Exogenous glutamine stimulated influx of ampicillin, leading to the accumulation of intracellular antibiotic concentrations that exceeded the amount tolerated by the multidrug-resistant bacteria. Furthermore, we demonstrated that exogenous glutamine promoted the biosynthesis of nucleosides including inosine, which in turn interacted with CpxA/CpxR and up-regulated OmpF. We validated the physiological relevance of the mechanism by showing that loss of , , , or elevated antibiotic resistance in antibiotic-sensitive strains. In addition, glutamine retarded the development of ampicillin resistance. These results may facilitate future development of effective approaches for preventing or managing chronic, multidrug-resistant bacterial infections, bacterial persistence, and difficult-to-treat bacterial biofilms.